2016
DOI: 10.4238/gmr.15027801
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 C118T polymorphism has predictive value for platinum-based chemotherapy in patients with late-stage bladder cancer

Abstract: ABSTRACT. This study aims to investigate the association between ERCC1 codon C118T polymorphism and the response rate of platinumbased chemotherapy in patients with late-stage bladder cancer. A total of 41 eligible patients histologically confirmed as having stage IV muscleinvasive transitional cell carcinoma of the bladder were treated with platinum-based chemotherapy for 2-6 cycles. The genotypes of patients were determined by PCR amplification of genomic DNA followed by restriction enzyme digestion. Positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Besides the genes involved in the DSB repair system, we are also interested in examining the contribution of the central NER repair protein, ERCC1, to the etiology of TNBC. The genotypes of ERCC1 have been shown to be associated with other types of cancer, including colorectal cancer [ 22 ], bladder cancer [ 47 ], esophageal cancer [ 48 ], but not breast cancer, not to mention TNBC. The accumulated case-control results in other types of cancer showed that the genotypes of ERCC1 may also contribute to TNBC, but this has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the genes involved in the DSB repair system, we are also interested in examining the contribution of the central NER repair protein, ERCC1, to the etiology of TNBC. The genotypes of ERCC1 have been shown to be associated with other types of cancer, including colorectal cancer [ 22 ], bladder cancer [ 47 ], esophageal cancer [ 48 ], but not breast cancer, not to mention TNBC. The accumulated case-control results in other types of cancer showed that the genotypes of ERCC1 may also contribute to TNBC, but this has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests polymorphisms in ERCC1 may help predict response to cisplatin and other platinum-based chemotherapeutics. Multiple ERCC1 single-nucleotide polymorphisms (SNPs) have been associated with platinum chemotherapy response [ 19 , 29 , 30 ]. A study investigating the role of three SNPs of ERCC1 in the clinical outcome of non-small-cell lung cancer (NSCLC) showed that the TT genotype of ERCC1 rs11615 and the AA genotype of rs3212986 polymorphisms were associated with an increased risk of death from NSCLC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…BC is one the most frequent urogenital malignancies in developed counties and some developing countries with rapid economic development (Xu et al, 2016[16]; Christoph et al, 2006[1]). There is evidence that modern lifestyles have strong association with the high incident of BC, which can induce epigenetic transformation, resulting in aberrant expression of some cancer-related genes (Romagnolo et al, 2016[7]; Shankar et al, 2016[9]).…”
Section: Discussionmentioning
confidence: 99%
“…Bladder carcinoma (BC) is one of most common malignancy in the economically advanced countries, and the incident of BC disease has been increasing rapidly in some developing countries, like China, in recent years (Xu et al, 2016[16]; Christoph et al, 2006[1]). The pathogenesis of BC remains unclear, but recent bioinformatics analysis and epidemiological study indicate that abnormal hypermethylation in promoter regions of many tumor suppressor genes blocks their expression, which attenuates effects of their gene products against tumorigenesis, resulting in increased risk of BC occurrence (Christoph et al, 2006[2]; JabƂonowski et al, 2011[3]; Meng et al, 2012[5]).…”
Section: Introductionmentioning
confidence: 99%